1985
DOI: 10.1017/s0266467400000286
|View full text |Cite
|
Sign up to set email alerts
|

Altitudinal zonation of forest vegetation on Mount Kerinci, Sumatra: with comparisons to zonation in the temperate region of east Asia

Abstract: The altitudinal zonation of forests on Mount Kerinci, Sumatra (3800 m) is described and compared with that in the temperate region of east Asia. Nine plots were selected between 1750 m in altitude and the upper limit of vegetation at 3250 m, at intervals of about 200 m in altitude. The plots are distinguished according to their main dominants, and the population structure of the dominant species is examined. The lower forests have species showing the whole range of size classes as well as solitary giants as do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
49
1
2

Year Published

1991
1991
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 12 publications
7
49
1
2
Order By: Relevance
“…On Costa Rican as well as on Colombian neotropical mountains, the diurnal climate is much more pronounced than the yearly cycle. The average temperature in Chirripó's cool-humid montane oak forests depends principally on elevation, as temperature decreases with increasing altitude.A drop of 0.57°C per 100-m increase in altitude is concordant with values estimated for other tropical mountains (Ohsawa et al 1985;Walter 1985;Kitayama 1992). Sub-soil temperatures on Chirripó change with elevation, and reflect annual air temperatures.…”
Section: Discussionsupporting
confidence: 84%
“…On Costa Rican as well as on Colombian neotropical mountains, the diurnal climate is much more pronounced than the yearly cycle. The average temperature in Chirripó's cool-humid montane oak forests depends principally on elevation, as temperature decreases with increasing altitude.A drop of 0.57°C per 100-m increase in altitude is concordant with values estimated for other tropical mountains (Ohsawa et al 1985;Walter 1985;Kitayama 1992). Sub-soil temperatures on Chirripó change with elevation, and reflect annual air temperatures.…”
Section: Discussionsupporting
confidence: 84%
“…Increasing precipitation and cloudiness tend to reduce treeline elevation. Ohsawa et al (1985) concluded that the``summer heat'' of higher latitudes is missing in the equatorial tropics and that the longer``season'' is not an adequate substitute for lower growth temperatures. Since these same factors also cause snowline elevation to decrease, there appears to be a common climatological reason for the parallel plateauing of the treeline and snowline curves in Fig.…”
Section: The Tropical Plateauing Of Treeline Altitudesmentioning
confidence: 99%
“…This means that MMT is independent of K and P and is a stable index for explaining the upper distributional limit of evergreen broadleaf forest. Kira (1971Kira ( , 1977, Ohsawa et al (1985) and Hattori and Nakanishi (1985) interpreted the upward distribution of the forest using CI. Ohsawa et al (1985) explained the upper limit of forests in mountainous regions in Asia in terms of the mean temperature for the coldest month.…”
Section: Validity Of Mmtmentioning
confidence: 99%
“…Kira (1971Kira ( , 1977, Ohsawa et al (1985) and Hattori and Nakanishi (1985) interpreted the upward distribution of the forest using CI. Ohsawa et al (1985) explained the upper limit of forests in mountainous regions in Asia in terms of the mean temperature for the coldest month. However, it was clear that the upper limit of the forest in mountainous regions in southwestern China could not be explained by either CI or mean temperature for the coldest month, as pointed out above.…”
Section: Validity Of Mmtmentioning
confidence: 99%
See 1 more Smart Citation